SAT0347 Baseline characteristics of patients with psoriatic arthritis initiated on apremilast in the corrona psoriatic arthritis/spondyloarthritis (PSA/SPA) registry. (12th June 2018) - Mease, P.J.; Rosenstein, E.; Feng, H.; Liu, M.; Guerette, B.; Teng, L.; Rebello, S.; Ogdie-Beatty, A.R.
Abstract : Background: Apremilast (APR) is an oral phosphodiesterase 4 inhibitor approved for the treatment of adult patients with active psoriatic arthritis (PsA) and psoriasis. Objectives: To characterise demographics, disease activity and duration, concomitant therapy, quality of life, and prior comorbidities among patients with PsA who initiated APR in the Corrona Psoriatic Arthritis/Spondyloarthritis (PsA/SpA) registry, an independent, prospective, US observational cohort. Methods: Adult patients≥18 years of age with PsA who were reported initiating APR in the Corrona PsA/SpA registry between May 2014 and September 2017 were included in the analysis. Descriptive statistics were calculated for patients' clinical characteristics and disease assessments at the index visit. The index visit was defined as the Corrona visit when APR initiation was reported. If the patient started a drug between 2 Corrona visits, the measures/outcomes from a prior visit were imputed to replace the missing values. Results: Among 138 patients included in the analysis, mean (SD) age was 56 12 years, mean (SD) BMI was 33, 7 62% were female, 66% were previously on a non-biologic DMARD (nbDMARD) and 79% had prior biologic use; 62% were on APR monotherapy. Of the APR initiators, the number of patients receiving concomitant methotrexate, nbDMARD, TNF inhibitor, and non-TNF inhibitor were 32 (23%), 41 (30%), 6 (4%), and 4 (3%), respectively. Pertinent comorbidities included diabetes mellitus (22%), metabolic syndrome (22%), cancer (18%), cardiovascular disease (17%), and congestive heart failure (0.7%). Patients reported a mean (SD) of 13 10 years for PsA symptoms and a mean (SD) of 10 9 years since PsA diagnosis. Of the 94 patients with data available for evaluation, 14% met criteria for minimal disease activity while 1% met criteria for very low disease activity. Most patients had moderate or low levels of disease activity, respectively: CDAI (48% and 35%), cDAPSA (47% and 34%), and DAS-28 (CRP) (37% and 21%). Of note, 82% of patients had <5 swollen joints and 63% had <5 tender joints. Mean HAQ-S (0–3) was 0.95 and BASDAI (0–10) was 5.4 (Table). Patients demonstrated a substantial burden of disease with a mean fatigue score (0–100) of 55 and mean overall pain score (0–100) of 55, and 81% reported stiffness lasting >30 min. Additionally, mean baseline work productivity and activity impairment (WPAI) subscale scores indicated limitations on absenteeism (8%), presenteeism (25%), work productivity loss (26%), and activity impairment (40%). Conclusions: The population of patients with PsA treated with APR in the Corrona PsA/SpA registry exhibited low to moderate disease activity and were substantially impacted, as evidenced by patient-reported outcomes (pain, fatigue, stiffness, and productivity). Future analyses on this cohort will provide more insight into patient characteristics and treatment patterns in this population, as well as long-term efficacy and safety information for PsA patients treated with APR. Disclosure of Interest: P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Genentech, Janssen, Eli Lilly, Pfizer, UCB, E. Rosenstein Grant/research support from: Biogen, Boehringer Ingelheim, Novartis, Consultant for: BMS, Boehringer Ingelheim, Speakers bureau: Amgen, BMS, H. Feng Employee of: Corrona, LLC, M. Liu Employee of: Corrona, LLC, B. Guerette Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, S. Rebello Employee of: Corrona, LLC, A. Ogdie-Beatty Grant/research support from: Pfizer, Novartis, Consultant for: Abbvie, BMS, Lilly, Pfizer, Novartis, Takeda